PENERAPAN METODE AHP DALAM PEMILIHAN ORGANISASI KEMAHASISWAAN - Yani, Fitri; Irawan, Devi; Andrika, Yuyi; Mayasari, Melati Suci (JUSIM (Jurnal Sistem Informasi Musirawas), 2023)
Students are an element that plays a significant role in the progress of higher education institutions. The role in question is in building ormawa. Ormawa is an organization to accommodate ideas for campus progress in accordance with the ormawa that it participates in. The organization chosen must be in accordance with the student's interests and talents. For this reason, research was carried out to build a decision support system in choosing ormawa. The method used is AHP (Analytical Hierarchy Process), this method is used for hierarchical multi-criteria attributes so that it is easier. After the data is obtained from the questionnaire results, the data is then processed into a pairwise matrix after which the consistency ratio value is calculated. The results of the research show that the alternative UKM Flow Map has a weight of 0.34, UKM Aoklah Production has a weight of 0.57, UKM LDK Atma Luhur has a weight of 0.16, and UKM Volly has a weight of 0.31.